Transcriptional regulation of core autophagy and lysosomal genes by the androgen receptor promotes prostate cancer progression. Issue 3 (4th March 2017) - Blessing, Alicia M.; Rajapakshe, Kimal; Reddy Bollu, Lakshmi; Shi, Yan; White, Mark A.; Pham, Alexander H.; Lin, Chenchu; Jonsson, Philip; Cortes, Constanza J.; Cheung, Edwin; La Spada, Albert R.; Bast, Robert C.; et al.
ABSTRACT: AR (androgen receptor) signaling is crucial for the development and maintenance of the prostate as well as the initiation and progression of prostate cancer. Despite the AR's central role in prostate cancer progression, it is still unclear which AR-mediated processes drive the disease. Here, we identified 4 core autophagy genes: ATG4B, ATG4D, ULK1, and ULK2, in addition to the transcription factor TFEB, a master regulator of lysosomal biogenesis and function, as transcriptional targets of AR in prostate cancer. These findings were significant in light of our recent observation that androgens promoted prostate cancer cell growth in part through the induction of autophagy. Expression of these 5 genes was essential for maximal androgen-mediated autophagy and cell proliferation. In addition, expression of each of these 5 genes alone or in combination was sufficient to increase prostate cancer cell growth independent of AR activity. Further, bioinformatic analysis demonstrated that the expression of these genes correlated with disease progression in 3 separate clinical cohorts. Collectively, these findings demonstrate a functional role for increased autophagy in prostate cancer progression, provide a mechanism for how autophagy is augmented, and highlight the potential of targeting this process for the treatment of advanced prostate cancer.